Evaluation of Porcine Versus Human Mesenchymal Stromal Cells From Three Distinct Donor Locations for Cytotherapy - Schweizer, Riccardo; Waldner, Matthias; Oksuz, Sinan; Zhang, Wensheng; Komatsu, Chiaki; Plock, Jan A.; Gorantla, Vijay S.; Solari, Mario G.; Kokai, Lauren; Marra, Kacey G.; Rubin, J. Peter (Frontiers in Immunology, 2020)
Background: Mesenchymal stromal cell (MSC)-based cytotherapies fuel the hope for reduction of chronic systemic immunosuppression in allotransplantation, and our group has previously shown this capability for both swine and human cells. MSCs harvested from distinct anatomical locations may have different behavior and lead to different outcomes in both preclinical research and human trials. To provide an effective reference for cell therapy studies, we compared human and porcine MSCs from omental fat (O-ASC), subcutaneous fat (SC-ASC) and bone marrow (BM-MSC) under rapid culture expansion with endothelial growth medium (EGM). Methods: MSCs isolated from pigs and deceased human organ donors were compared for yield, viability, cell size, population doubling times (PDT), surface marker expression and differentiation potential after rapid expansion with EGM. Immunosuppressant toxicity on MSCs was investigated in vitro for four different standard immunosuppressive drugs. Immunomodulatory function was compared in mixed lymphocyte reaction assays (MLR) with/without immunosuppressive drug influence. Results: Human and porcine omental fat yielded significantly higher cell numbers than subcutaneous fat. Initial PDT was significantly shorter in ASCs than BM-MSCs and similar thereafter. Viability was reduced in BM-MSCs. Porcine MSCs were positive for CD29, CD44, CD90, while human MSCs expressed CD73, CD90 and CD105. All demonstrated confirmed adipogenic differentiation capacity. Cell sizes were comparable between groups and were slightly larger in human cells. Rapamycin revealed slight, mycophenolic acid strong and significant dose-dependent toxicity on viability/proliferation of almost all MSCs at therapeutic concentrations. No relevant toxicity was found for Tacrolimus and Cyclosporin A. Immunomodulatory function was dose-dependent and similar between groups. Immunosuppressants had no significant adverse effect on MSC immunomodulatory function. Discussion: MSCs from different harvest locations and donor species differ in terms of isolation yields, viability, PDT, and size. We did not detect relevant differences in immunomodulatory function with or without the presence of immunosuppressants. Human and pig O-ASC, SC-ASC and BM-MSC share similar immunomodulatory function in vitro and warrant confirmation in large animal studies. These findings should be considered in preclinical and clinical MSC applications.